2020
DOI: 10.1016/j.jgr.2019.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Cold-induced ginsenosides accumulation is associated with the alteration in DNA methylation and relative gene expression in perennial American ginseng (Panax quinquefolius L.) along with its plant growth and development process

Abstract: Background Ginsenosides accumulation responses to temperature are critical to quality formation in cold-dependent American ginseng. However, the studies on cold requirement mechanism relevant to ginsenosides have been limited in this species. Methods Two experiments were carried out: one was a multivariate linear regression analysis between the ginsenosides accumulation and the environmental conditions of American ginseng from different sites of China and the other was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…As with other medicinal plants, the production of saponin-containing plants, especially their secondary metabolites, significantly depends on the geographical zone, cultivation site, and different biotic and abiotic factors in the habitat, both qualitatively and quantitatively [ 18 ]. Ginsenosides production is influenced by different abiotic stresses like temperature [ 18 ], light, [ 104 ], drought [ 105 , 106 ], and salinity [ 107 ]. The production of secondary metabolites may also be altered by environmental stresses [ 108 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As with other medicinal plants, the production of saponin-containing plants, especially their secondary metabolites, significantly depends on the geographical zone, cultivation site, and different biotic and abiotic factors in the habitat, both qualitatively and quantitatively [ 18 ]. Ginsenosides production is influenced by different abiotic stresses like temperature [ 18 ], light, [ 104 ], drought [ 105 , 106 ], and salinity [ 107 ]. The production of secondary metabolites may also be altered by environmental stresses [ 108 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among them, ginsenosides, also known as triterpene glycoside saponin, are most common and well known in pharmacological and physiological fields as a remedial of anticancer, antidiabetic, immunomodulatory, neuroprotective, radioprotective, antiamnestic, and antistress [ 16 ]. Earlier it was well described that ginsenosides content in ginseng plants varies depending on factors like light, water, temperature, ionizing radiation, soil, location, plant age, and so on [ 18 , 19 , 20 ]. Salt stress is also a crucial factor that affects the growth, development and yield of ginseng plants [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that ROS1 expression is promoted by DNA methylation and antagonized by DNA demethylation [ 61 ], and ROS1 expression is also inhibited in RdDM silencing and in met1 mutants [ 61 ]. Moreover, there is a cyclically reversible dynamism between DNA methylation and DNA demethylation during the temperature seasonality response in perennial American ginseng [ 62 ], which suggests that DNA methylation and demethylation are dynamic processes in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Developmental methylome of the medicinal plant Cape periwinkle ( Catharanthus roseus ) determined that cellular and physiological functions are likely to be impacted by tissue-specific covariations between context-dependent DNA methylation ( Dugé de Bernonville et al., 2020 ). The cold environment affected ginsenosides accumulation in perennial American ginseng ( Panax quinquefolium ), and a cyclically reversible dynamism between methylation and demethylation of DNA was also reported in response to temperature seasonality ( Hao et al., 2020 ). Further investigations of medicinal plant pan-genomes and epigenomes addressing bioactive compound metabolism are needed to improve the production of secondary metabolites for pharmaceutical applications.…”
Section: Advancing Comparative Genomics Genetic Mapping Pan-genome An...mentioning
confidence: 99%